2019
DOI: 10.1002/app.47698
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the structure of Kevlar nanofiber and its effects on the mechanical property and thermal stability of carboxylated acrylonitrile butadiene rubber

Abstract: Water‐dispersible hydrolyzed Kevlar nanofibers (hANFs) prepared by acid‐assisted hydrothermal treatments of Kevlar nanofibers (ANFs) were first incorporated into carboxylated acrylonitrile butadiene rubber (XNBR) by a latex co‐coagulation method. The obtained hANFs maintained the one‐dimensional nanofibrous morphology and crystal structure as ANFs. There were amounts of polar groups appearing at the end of hANFs molecular chains after hydrothermal process, which led to the strong hydrogen bonding interaction b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…2. For mANFs, a strong diffraction peak at 2θ = 20.7° and a shoulder peak at 2θ = 23.5° displayed in the diffraction pattern, corresponding to the (110) and (200) planes of the ANF crystals, respectively [47]. The amorphous neat EA exhibited a diffused diffraction peak centred at 2θ = 19.5°.…”
Section: Structure and Morphological Investigation Of Ea/manf Nanocom...mentioning
confidence: 98%
See 1 more Smart Citation
“…2. For mANFs, a strong diffraction peak at 2θ = 20.7° and a shoulder peak at 2θ = 23.5° displayed in the diffraction pattern, corresponding to the (110) and (200) planes of the ANF crystals, respectively [47]. The amorphous neat EA exhibited a diffused diffraction peak centred at 2θ = 19.5°.…”
Section: Structure and Morphological Investigation Of Ea/manf Nanocom...mentioning
confidence: 98%
“…Thus, ANF has attracted considerable attention in composite reinforcement, exible electronics, and battery separators. Research has revealed that ANF can effectively improve the mechanical performance of polymers, such as epoxy resin [40][41][42][43], rubber [44][45][46][47],…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the ANF has abundant amide groups on surface, enabling it to be an ideal reinforcement for developing polymer–polymer nanocomposites. A fraction of ANF can substantially reinforce polar polymer materials because of efficient stress transfer from the nanofiber to polymer matrix. , On the other hand, it is reported that pure ANF film has excellent mechanical strength and toughness because of physical entanglement and strong hydrogen-bond interaction between the nanofibers . This implies that ANF would be an excellent polymeric building block as a matrix for constructing advanced inorganic–polymer composite materials. …”
mentioning
confidence: 99%
“…22,23 Jia et al successfully prepared ANF-reinforced styrene-butadiene rubber and ANFreinforced carboxylated acrylonitrile butadiene rubber, which demonstrated that ANF has an excellent reinforcement effect to rubber. [24][25][26] ANF is also applied to enhance the interface properties between the fiber and the polymer matrix. 27,28 Through electrostatic interaction, ANFs are deposited on the surface of fibers, and the interfacial adhesion of the fiber is improved by increasing the surface roughness of the fiber.…”
Section: Introductionmentioning
confidence: 99%
“…Aramid nanofiber (ANF), which possess the advantages of high aspect ratio, large specific area, and good mechanical properties, has been successfully prepared through various methods 22,23 . Jia et al successfully prepared ANF‐reinforced styrene‐butadiene rubber and ANF‐reinforced carboxylated acrylonitrile butadiene rubber, which demonstrated that ANF has an excellent reinforcement effect to rubber 24–26 . ANF is also applied to enhance the interface properties between the fiber and the polymer matrix 27,28 .…”
Section: Introductionmentioning
confidence: 99%